2016
DOI: 10.12738/estp.2016.6.0015
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Multiple Intelligences Theory-Based Education on Academic Achievement: A Meta-Analytic Review

Abstract: The main purpose of this study is to determine the effect of multiple intelligences theory (MIT)-based education on students' academic achievement. In this research, the meta-analytic method was adopted to determine this effect, and studies related to this subject carried out in Turkey were compiled. The effect sizes of the studies included in the meta-analysis were compared in terms of the variables of educational level, course type, being a postgraduate thesis or doctoral dissertation, geographical region, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
(53 reference statements)
0
9
0
Order By: Relevance
“…Previous scholars have undertaken many meta-analysis articles on the creation of multiple intelligence concepts. Previous studies showed in the analysis that the multiple intelligence concept has a profound and optimistic effect on academic pursuits [9], [12]. This increase is in line with the increasing application period.…”
Section: Introductionmentioning
confidence: 59%
“…Previous scholars have undertaken many meta-analysis articles on the creation of multiple intelligence concepts. Previous studies showed in the analysis that the multiple intelligence concept has a profound and optimistic effect on academic pursuits [9], [12]. This increase is in line with the increasing application period.…”
Section: Introductionmentioning
confidence: 59%
“…Most of the published classroom studies found improved learning through use of MI teaching methods. Bas (2016) , Batdi (2017) , and Ferrero et al (2021) conducted meta-analyses of studies of the effectiveness of using MI in the classroom, and all three meta-analyses reported many studies with positive results for MI teaching. Some MI teaching strategies have focused on teaching students the different intelligences.…”
Section: Problems For Studies Of MI Teaching Strategiesmentioning
confidence: 99%
“…This method unquestionably offers educators a new view point. This concept is significant because it emphasizes individual difference rather than assigning intelligence to individuals [ 27 ]. When students receive teaching that is appropriate for their intellectual type, academic success increases.…”
Section: Introductionmentioning
confidence: 99%
“…When students receive teaching that is appropriate for their intellectual type, academic success increases. Conversely, students find it difficult to learn when their education does not match the way they learn [ 28 ].…”
Section: Introductionmentioning
confidence: 99%